2019
DOI: 10.1212/wnl.0000000000008007
|View full text |Cite
|
Sign up to set email alerts
|

New and expanding ventricular hemorrhage predicts poor outcome in acute intracerebral hemorrhage

Abstract: ObjectiveTo describe the relationship between intraventricular hemorrhage (IVH) expansion and long-term outcome and to use this relationship to select and validate clinically relevant thresholds of IVH expansion in 2 separate intracerebral hemorrhage (ICH) populations.MethodsWe used fractional polynomial analysis to test linear and nonlinear models of 24-hour IVH volume change and clinical outcome with data from the Predicting Hematoma Growth and Outcome in Intracerebral Hemorrhage Using Contrast Bolus CT (PRE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 27 publications
4
53
1
Order By: Relevance
“…Hypodensities and black hole sign could be regarded as useful predictors in ICH in our study. Recent studies found that intraventricular hemorrhage and intraventricular hemorrhage expansion were strongly predictive of poor outcome in ICH [20,21]. However, intraventricular hemorrhage was not independently associated with poor outcome in our study.…”
Section: Discussioncontrasting
confidence: 85%
“…Hypodensities and black hole sign could be regarded as useful predictors in ICH in our study. Recent studies found that intraventricular hemorrhage and intraventricular hemorrhage expansion were strongly predictive of poor outcome in ICH [20,21]. However, intraventricular hemorrhage was not independently associated with poor outcome in our study.…”
Section: Discussioncontrasting
confidence: 85%
“…We hypothesise haematoma expansion and early neurological deterioration likely account for the improved performance of delayed ICH scores. [18][19][20] The observed improvement in mortality prognostication is consistent with previous published work, 6 21 22 and these results advise against early prognostication, which is in accordance with current American Heart Association guidelines. 5 Our findings are important for clinical practice, as discussions around withdrawal of care in ICH typically occur days after admission, with the average decision to institute withdrawal of care orders around day 5.…”
Section: Open Accesssupporting
confidence: 91%
“…With regard to its effect on outcome, IVH is not an "all or nothing" event. Increasing degrees of IVH correlate with an increasing risk of worse outcome [27][28][29][30]. These findings suggest that there might be a subgroup of patients with ICH in whom ICH is diagnosed early enough to potentially prevent IVH or contain an early stage IVH through blood pressure control or surgical intervention [12,31].…”
Section: Discussionmentioning
confidence: 99%